Karakteristik Minyak Jagung Varietas Lokal Madura - Indarto, Cahyo; Maflahah, Iffan; Fakhry, Muhammad; ., Sugiharto (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 11 No 1 (2023): MaretDO - 10.24843/JRMA.2023.v11.i01.p14, 2023)
T he recent problems of production and distribution of palm oil have caused the price of cooking oil to soar very high recently, not only having an impact on the economy but also social turmoil. Corn is a source of food oil that can be cultivated throughout Indonesia. In fact, corn oil has more health value than palm oi l . This study aims to characterize the quality of corn oil extracted from various local varieties of Madura. Madura is one of the important corn producers in East Java province. N-hexane is used as a solvent for the extraction of corn oil. The results showed that variations in corn varieties produced corn oil with different quality parameters (p 0.05). The average yield of corn oil from various local Madura varieties ranged from 21.53% to 25.14%, with the Batu Putih variety producing the highest yield. Meanwhile, the quality parameters ( specific gravity, peroxide number and free fatty acid ) in this research did not meet the SNI standards for corn oil.